Answer:
The equivalent expression to the givan expression is
[tex]\sqrt[4]{324m^{12}}\times\sqrt[3]{64k^9}=12\sqrt[4]{4}m^3k^3[/tex]
Step-by-step explanation:
Given expression is 4th root of 324m^12 * the cubed root of 64k^9
The given expression can be written as
[tex]\sqrt[4]{324m^{12}}\times\sqrt[3]{64k^9}[/tex]
To find the equivalent expression to the given expression :
[tex]\sqrt[4]{324m^{12}}\times\sqrt[3]{64k^9}[/tex]
[tex]=\sqrt[4]{81\times 4m^{12}}\times\sqrt[3]{16\times 4k^9}[/tex]
[tex]=\sqrt[4]{3\times 3\times 3\times 3\times 4m^{12}}\times\sqrt[3]{4\times 4\times 4k^9}[/tex]
[tex]=\sqrt[4]{3\times 3\times 3\times 3\times 4m^{12}}\times\sqrt[3]{4\times 4\times 4k^9}[/tex]
[tex]=(3\times \sqrt[4]{m^{12}})\times (4\times \sqrt[3]{k^9})[/tex]
[tex]=(3\times \sqrt[4]{4m^{12}})\times (4\times \sqrt[3]{k^9})[/tex]
[tex]=(3\times \sqrt[4]{4}\times (m^{12})^{\frac{1}{4}})\times (4\times {(k^9)^{\frac{1}{3}})[/tex]
[tex]=(3\sqrt[4]{4}\times m^{\frac{12}{4}})\times (4\times k^{\frac{9}{3}})[/tex]
[tex]=(3\sqrt[4]{4}\times m^3)\times (4\times k^3)[/tex]
[tex]=3\sqrt[4]{4}m^3.4k^3[/tex]
[tex]=12\sqrt[4]{4}m^3k^3[/tex]
[tex]\sqrt[4]{324m^{12}}\times\sqrt[3]{64k^9}=12\sqrt[4]{4}m^3k^3[/tex]
Therefore the equivalent expression to the given expression is
[tex]\sqrt[4]{324m^{12}}\times\sqrt[3]{64k^9}=12\sqrt[4]{4}m^3k^3[/tex]